2021
DOI: 10.1039/d0ra08487e
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant cuttlefish collagen hydrolysate against ethyl carbamate-induced oxidative damage

Abstract: Collagen hydrolysate against EC-induced oxidative damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Alpha lipoic acid also ameliorated cobalt-induced liver injury via inhibiting ferroptosis [ 130 ]. In addition, ammonia [ 131 ], lead [ 132 ], mercuric chloride [ 133 ], ethyl carbamate [ 134 , 135 ], di (2-ethylhexyl) phthalate [ 136 ], aflatoxin B1 [ 137 ], and acrylamide [ 138 ] could cause liver injury by inducing ferroptosis. And there are corresponding NAC to prevent or treat pollutants-induced liver injury ( Table 1 ).…”
Section: Nac Treat Liver Disease By Targeting Ferroptosismentioning
confidence: 99%
“…Alpha lipoic acid also ameliorated cobalt-induced liver injury via inhibiting ferroptosis [ 130 ]. In addition, ammonia [ 131 ], lead [ 132 ], mercuric chloride [ 133 ], ethyl carbamate [ 134 , 135 ], di (2-ethylhexyl) phthalate [ 136 ], aflatoxin B1 [ 137 ], and acrylamide [ 138 ] could cause liver injury by inducing ferroptosis. And there are corresponding NAC to prevent or treat pollutants-induced liver injury ( Table 1 ).…”
Section: Nac Treat Liver Disease By Targeting Ferroptosismentioning
confidence: 99%
“…In addition, collagen gel application reduced infection and accelerated epithelialization. Furthermore, it has been demonstrated that the abundant methionine residues within the peptide chain of marine collagen hydrolysate serve as active sites for antioxidant activity [ 193 ]. Besides, it could scavenge ROS by inhibiting the ferroptosis signal pathway and depleting antioxidant GSH molecules, thereby enhancing cell viability when applied to tissue injury and aiding in the resistance to oxidation-induced cell death.…”
Section: Marine Structural Protein-based Nanocarriersmentioning
confidence: 99%
“…Another category of marine collagen falls under invertebrate animals. Antioxidant collagen hydrolysates isolated from invertebrate animals including squid [48], rhopilema hispidum, sea cucumber and cuttlefish, have been found with a variety of biomedical activities [34,49,50]. They can also serve as marine source of antioxidant collagen hydrolysates for medicinal use.…”
Section: Species As Collagen Sourcesmentioning
confidence: 99%
“…For example, the optimal extraction conditions for a high antioxidant collagen hydrolysate from cuttlefish skin using alcalase were based on the single-factor analysis. A common process condition optimization method, Box-Behnken design, was used to optimize the operating variables such as temperature, pH, and enzyme quantity [34]. Moreover, a combination ABTS radical scavenging of enzymes leverages the advantages of multiple enzymes, resulting in higher antioxidant activities of collagen hydrolysates.…”
Section: The Design Of the Hydrolysis Reaction To Obtain Antioxidant ...mentioning
confidence: 99%